Improving Branch Prediction Performance with a Generalized Design for Dynamic Branch Predictors - M. Lin, W.; Madhavaram, R.; Y. Yang, A. (Informatica)
Improving Branch Prediction Performance with a Generalized Design for Dynamic Branch Predictors